2020
DOI: 10.1109/access.2020.2977688
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Contact Game Using Mixed Reality for the Treatment of Children With Attention Deficit Hyperactivity Disorder

Abstract: Many children with attention deficit hyperactivity disorder (ADHD) perform poorly in their academic studies. They also have difficulties in their social lives due to a lack of interpersonal skills and this often continues into adult life. Appropriate early therapies and medications can be very beneficial. In this paper, we introduce and demonstrate the benefits of a new type of treatment, namely, an eye-contact game which successfully exploits mixed reality technology. None of the patients in our experiment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…The results revealed that other learners’ skills beyond demographics such as self-regulation, spatial cognition and mental rotation should be considered 20 Kaimara et al ( 2020a , b ) Research article * * The main objective focused on the correlation of the University students’ views that were sharing common characteristics, like gender, information and communication technology skills, game playing experience, and specific scientific background with factors that related to the gameplay as well as the learning effectiveness 21 Kenny and Gunter ( 2011 ) Research article * Video games are one of the fastest-growing elements of informal, virtual learning. In this article, the authors presented a design and evaluation rubric that appears to overcome many of the shortcomings in educational games currently on the market 22 Kim et al ( 2020 ) Research article * In this paper, the authors introduced and demonstrated the benefits of a new type of treatment, namely, an eye-contact game that successfully exploits mixed reality technology with head-mounted display. ADHD children, after participating in the treatment sessions, the omission/commission errors which were evaluated in an attention test decreased significantly 23 Koops et al ( 2016 ) Research article * * Computer games, based on physics simulations, have been utilized to provide an alternative learning tool.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results revealed that other learners’ skills beyond demographics such as self-regulation, spatial cognition and mental rotation should be considered 20 Kaimara et al ( 2020a , b ) Research article * * The main objective focused on the correlation of the University students’ views that were sharing common characteristics, like gender, information and communication technology skills, game playing experience, and specific scientific background with factors that related to the gameplay as well as the learning effectiveness 21 Kenny and Gunter ( 2011 ) Research article * Video games are one of the fastest-growing elements of informal, virtual learning. In this article, the authors presented a design and evaluation rubric that appears to overcome many of the shortcomings in educational games currently on the market 22 Kim et al ( 2020 ) Research article * In this paper, the authors introduced and demonstrated the benefits of a new type of treatment, namely, an eye-contact game that successfully exploits mixed reality technology with head-mounted display. ADHD children, after participating in the treatment sessions, the omission/commission errors which were evaluated in an attention test decreased significantly 23 Koops et al ( 2016 ) Research article * * Computer games, based on physics simulations, have been utilized to provide an alternative learning tool.…”
Section: Resultsmentioning
confidence: 99%
“…The increased Internet use and media sources produce abnormal patterns of behaviour which may reflect symptoms similar to ADHD-like behaviours (Steve and Grubb 2018 ). Contrariwise, promising results were found early enough regarding the rehabilitation of inattention and impulsiveness through VR (Cho et al 2004 ; Kim et al 2020 ). Cho et al studied twenty-eight participants aged 14–18 years who had learning difficulties and presented inattentive, impulsive, hyperactive, and distracted behaviour without official ADHD diagnosis and found that participants were reducing the level of inattention and impulsiveness through the immersive VR interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies which support ADHD treatments have been developed in recent years. For example [28] presents an eyecontact game that uses mixed reality for the treatment of children diagnosed with ADHD. This interactive game helps to significantly reduce the omission errors carried out when the children were evaluated by an attention test, instead of children who resolved the same attentional test without using this innovative game.…”
Section: Related Workmentioning
confidence: 99%